Validation of the Dutch Version of the Boston Carpal Tunnel Questionnaire - De Kleermaeker, Floriaan G. C. M.; Levels, Mark; Verhagen, Wim I. M.; Meulstee, Jan (Frontiers in Neurology, 2019)
The Boston Carpal Tunnel Questionnaire (BCTQ) is a scale that has been developed specifically for carpal tunnel syndrome (CTS). It consists of the Functional Status Scale (FSS) and the Symptom Severity Scale (SSS). It is the most widely used patient reported outcome measure in CTS and has been validated in many languages. Although already widely used, psychometric properties of the Dutch version of the BCTQ are yet unknown. Aim of this study was to assess the validity, reliability, responsiveness and acceptability of the Dutch version. A total of 180 patients completed the BCTQ in addition to a six-point Likert scale for perceived improvement, before and about 6-8 months after carpal tunnel release (CTR). Principal factor analysis revealed that the FSS is unidimensional, consisting of a single latent factor (“functionality”) and has a high internal consistency (Cronbach’s α = .825). However, the SSS has 3 dimensions which are all highly internally consistent: “daytime symptoms” (Cronbach’s α = 0.805), “nighttime symptoms” (Cronbach’s α = 0.835) and “operational capacity” (Cronbach’s α = 0.723). Post-treatment, the FSS still consisted of one factor, but the SSS changed in dimensionality, as it had only 2 factors left post-treatment. The ∆FSS and ∆SSS had good correlation with the six-point Likert scale for perceived improvement (r = 0.524; p<0.01 and 0.574; p<0.01, respectively), a moderate correlation between FSS and pinch grip (r = 0.259; p<0.01) was found, and a weak correlation between SSS and pinch grip (r = 0.231; p<0.01). Standard Response Mean for FSS and SSS was 0.76 and 1.49, respectively. Effect Size was 0.92 and 1.96, respectively, both indicating a good responsiveness. Response rate was high (82-84%). We concluded that the Dutch version of the BCTQ has a proper reliability, validity, responsiveness and acceptability to assess the symptom severity and functional disabilities of CTS patients. Because of multidimensionality, we would recommend to create sum scores of the 4 different dimensions instead of 2. Caution is required when interpreting the results postoperatively, due to the insufficient longitudinal (the use after an intervention) validity of the SSS.